Systematic Review: The Effectivity of Sustainability Reporting on Firm Value - Andi Arjuni K; Arifuddin; Syamsuddin; Ratna Ayu Damayanti (IECON: International Economics and Business Conference, 2023)
As the company's development continues to increase, companies are expected to disclose reporting on the impactof ESG. To maintain the sustainability of the ecosystem, a sustainability report is needed. This study aims to empirically testthe effectiveness of sustainability reporting on firm value by using a literature review on the Scopus journal index with identified 200 articles Scopus published between 2015-2022. Then it evaluated by using PRISMA based on predetermined criteria. The results showed various findings. Sustainability reporting has negative impact in social and environment in banking sector but has positive significant in manufacturing sector and tourism sector.